Physiological evidence of stress reduction during a summer Antarctic expedition with a significant influence of previous experience and vigor - Ráčková, Lucie; Pompa, Tomáš; Zlámal, Filip; Barták, Miloš; Nývlt, Daniel; Bienertová-Vašků, Julie (Scientific reports, 2024)
Antarctica provides a unique environment for studying human adaptability, characterized by controlled conditions, limited sensory stimulation, and significant challenges in logistics and communication. This longitudinal study investigates the relationship between stress indicators, with a specific focus on mean sleep heart rate, during a COVID-19 quarantine and subsequent 83 days long summer Antarctic expedition at the J. G. Mendel Czech Antarctic Station. Our novel approach includes daily recordings of sleep heart rate and weekly assessments of emotions, stress, and sleep quality. Associations between variables were analyzed using the generalized least squares method, providing unique insights into nuances of adaptation. The results support previous findings by providing empirical evidence on the stress reducing effect of Antarctic summer expedition and highlight the importance of previous experience and positive emotions, with the novel contribution of utilizing physiological data in addition to psychological measures. High-frequency sampling and combination of psychological and physiological data addresses a crucial gap in the research of stress. This study contributes valuable knowledge to the field of psychophysiology and has implications for expedition planners, research organizations, teams in action settings, pandemic prevention protocols, global crises, and long-duration spaceflight missions. Comprehensive insights promote the well-being and success of individuals in extreme conditions.
Keywords: longitudinální studie; psychofyziologie; Humans; expedice; Expeditions; Antarktida; Antarctic Regions; Sleep; lidé; Psychophysiology; Longitudinal Studies; spánek